Wave Transmission and Energy Dissipation in a Box Culvert-Type Slotted Breakwater - Nastain; Suripin; Yuwono, Nur; Sriyana, Ignatius (Advances in Technology Innovation, 2022)
This research is conducted to examine the transmission wave and energy dissipation of a box culvert-type slotted breakwater, which is designed as a breakwater structure with a watertight wall at the top and a box culvert type hole at the bottom. The process involves physical modeling of this structure in the laboratory. The hole and wave parameters are varied to determine the breakwater performance. The results show that the transmission coefficient (KT) value is reduced as the relative hole height (hL/d) value is decreasing and the relative hole length (B/L) and wave steepness (H/L) values are increasing. The energy dissipation coefficient (KD) value increases with an increment in hL/d, H/L, and B/L but starts to decrease after reaching the maximum, which is the optimum H × B/L2 value. This optimum value is found to be 0.0034(hL/d)2.618 depending on the (hL/d) value, while the maximum KD value is recorded to be 0.70.